2011
DOI: 10.1055/s-0030-1256961
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided anterograde treatment of biliary stones following gastric bypass

Abstract: Endoscopic treatment of bile duct stones in gastric bypass patients is challenging. We describe a novel method involving endoscopic ultrasound (EUS)-guided anterograde interventions. After prior experience with EUS-guided rendezvous endoscopic retrograde cholangiopancreatography (ERCP) and direct EUS-guided anterograde stenting for malignant biliary obstruction, we have attempted EUS-guided treatment of biliary stones as first-line therapy following gastric bypass. Our approach involves: (i) EUS-fine needle as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 10 publications
0
55
0
1
Order By: Relevance
“…In the previous studies by Weilert et al. and Iwashita et al. , there was no precise information regarding the size, number, diameter of the stone and the shape of the bile duct.…”
Section: Discussionmentioning
confidence: 94%
“…In the previous studies by Weilert et al. and Iwashita et al. , there was no precise information regarding the size, number, diameter of the stone and the shape of the bile duct.…”
Section: Discussionmentioning
confidence: 94%
“…Throughout the entire procedure, it is important to maintain the original echoendoscope tip position used when the bile duct was accessed with the FNA needle and close apposition of the tip with the intestinal lumen by using both ultrasound and fluoroscopic guidance, especially if using an oblique viewing scope. The main concern with this antegrade approach is bile leak from the temporary enterobiliary fistula [36-38]. Placement of a second transhepatic stent or a nasobiliary drain following antegrade balloon dilation is optional, and it is unclear whether these additional steps decrease bile leak from the transmural puncture site.…”
Section: Therapeutic Eusmentioning
confidence: 99%
“…A few case series reviewed the use of EUS-guided antegrade biliary drainage in patients with both normal anatomy and SAA [36,37,39,40]. In these small studies, the technical success rate ranged from 67% to 100% for the entire cohort, with a clinical success rate of approximately 78%.…”
Section: Therapeutic Eusmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported technical success of EUS-guided anterograde balloon sphincteroplasty and anterograde stone extraction in 4 out of 6 patients. 24 Park do and colleagues 25 have described a case report of EUS-guided transhepatic anterograde balloon dilation for a benign bilioenteric anastomotic stricture. The available data on EUS-guided downstream transductal interventions are summarized in Table 2.…”
Section: Anterograde Access and Downstream Transductal Drainagementioning
confidence: 99%